2015
DOI: 10.1074/jbc.m115.645812
|View full text |Cite
|
Sign up to set email alerts
|

Human Urinary Composition Controls Antibacterial Activity of Siderocalin*

Abstract: Background: During urinary tract infections, humans secrete the protein siderocalin to block bacterial iron uptake. Results: Human urinary pH and metabolite composition strongly affect siderocalin's antibacterial activity. Conclusion: Siderocalin uses a subset of urinary metabolites as cofactors to withhold iron from E. coli in competition with the bacterial siderophore enterobactin. Significance: Therapeutic control of urinary composition may facilitate an important innate antibacterial defense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 53 publications
5
84
0
Order By: Relevance
“…[6][7][8][9] In particular UPEC have evolved a complex mechanism to chelate iron via siderophores, and several studies have revealed that UPEC have more iron chelators than most bacterial pathogens. 7,[9][10][11][12][13] Consistent with this, UPEC growth is impeded if the bacteria are prevented from acquiring iron. 6,9,14 However, eukaryotic cells have evolved elaborate methods of iron sequestration, storage, and release.…”
Section: Introductionmentioning
confidence: 53%
“…[6][7][8][9] In particular UPEC have evolved a complex mechanism to chelate iron via siderophores, and several studies have revealed that UPEC have more iron chelators than most bacterial pathogens. 7,[9][10][11][12][13] Consistent with this, UPEC growth is impeded if the bacteria are prevented from acquiring iron. 6,9,14 However, eukaryotic cells have evolved elaborate methods of iron sequestration, storage, and release.…”
Section: Introductionmentioning
confidence: 53%
“…All participants provided written informed consent for the sample collection and following analysis, prior to inclusion in the study. Study design, inclusion and exclusion criteria, and sample preparation were previously described (14,86). β-Hemolytic E. coli isolates from urine cultures with 10 5 or more CFU/ml were selected from the cohort for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…These studies, combining chemical screening 54 and natural product approaches proved the putative ligands as naturally occurring iron “buffers” in the human urine 66 . Using a LC-MS based metabolomic analysis, catechols have been further confirmed existing in human urine and controlling urinary NGAL antimicrobial activity recently 67 . The combination of the three studies support the notion that simple catechols should be considered naturally occurring binding partners of NGAL.…”
Section: The Ligands Of Ngalmentioning
confidence: 97%
“…Detailed reviews and comments on the catechols could be found in different journals 17,64–67 . In the study, simple catechols such as catechol ( 51 ), 3-methylcatechol ( 52 ), 4-methylcatechol ( 53 ), and pyrogallol ( 54 ) (Fig.…”
Section: The Ligands Of Ngalmentioning
confidence: 99%